2006
DOI: 10.1073/pnas.0509634103
|View full text |Cite
|
Sign up to set email alerts
|

Strength of early visual adaptation depends on visual awareness

Abstract: We measured visual-adaptation strength under variations in visual awareness by manipulating phenomenal invisibility of adapting stimuli using binocular rivalry and visual crowding. Results showed that the threshold-elevation aftereffect and the translational motion aftereffect were reduced substantially during binocular rivalry and crowding. Importantly, aftereffect reduction was correlated with the proportion of time that the adapting stimulus was removed from visual awareness. These findings indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
148
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(180 citation statements)
references
References 52 publications
29
148
1
2
Order By: Relevance
“…After all, in other circumstances suppression durations of a visual stimulus are impacted by the properties of that stimulus, including its physical characteristics (9), its configural properties (30,66), its affective connotation (67,68), its lexical familiarity (32), and its social connotation (69). However, in all these instances the features defining the suppressed stimulus are plausibly being registered and remain available for analysis (70), albeit with reduced fidelity or signal strength (34). There is no reason why this should not be true for the visual features-contour size, orientation and contrast polarity-comprising notes contained in the musical scores used as a rival stimulus in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…After all, in other circumstances suppression durations of a visual stimulus are impacted by the properties of that stimulus, including its physical characteristics (9), its configural properties (30,66), its affective connotation (67,68), its lexical familiarity (32), and its social connotation (69). However, in all these instances the features defining the suppressed stimulus are plausibly being registered and remain available for analysis (70), albeit with reduced fidelity or signal strength (34). There is no reason why this should not be true for the visual features-contour size, orientation and contrast polarity-comprising notes contained in the musical scores used as a rival stimulus in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all the adaptation effects we found in the visible condition were independent of motion strength (i.e., ISI for apparent motion, and walking speed for biological motion), and adaptation to apparent motion was constant despite the linear decrease in the subjective motion strength. The fact that adaptation does not decrease with motion strength is probably due to the existence of a compressive nonlinearity, with adaptation response saturating at high motion strength (Blake, Tadin, Sobel, Raissian, & Chong, 2006). Similarly, the fact that adaptation to visible and invisible apparent motion was of similar amplitude at high motion strength (i.e., ISI = 100 ms) is likely due to response saturation, which in this case would conceal the decrease of sensitivity under CFS (the saturation of adaptation responses is unlikely in case of biological motion, since the effect amplitude differed between the visible and invisible condition).…”
Section: Discussionmentioning
confidence: 99%
“…To completely suppress the adaptors, dynamic radial gratings were used as suppressors, alternating between clockwise and counterclockwise rotation at 1 Hz. These suppressors do not produce motion-or orientation-specific aftereffects (Blake et al, 2006). Two sinusoidal gratings (adaptors) were presented to the left and the right visual field of the nondominant eye, and two radial gratings (suppressors) were presented to the left and the right visual fields of the dominant eye.…”
Section: Methodsmentioning
confidence: 99%
“…Postadaptation contrast measurements, with exactly the same procedure as the baseline-contrast threshold measurements (except that now the number of trials was fixed), were interleaved with top-up adaptation periods. We did not use different orientations for the test stimuli, since a previous study with a similar method had shown this aftereffect was orientation specific (Blake et al, 2006).…”
Section: Methodsmentioning
confidence: 99%